2012
DOI: 10.1017/s0033822200047603
|View full text |Cite
|
Sign up to set email alerts
|

14C Marine Reservoir Variability in Herbivores and Deposit-Feeding Gastropods from an Open Coastline, Papua New Guinea

Abstract: ABSTRACT. Herbivorous and deposit-feeding gastropods are a major component of archaeological shell middens worldwide. They provide a wealth of information about subsistence, economy, environment, and climate, but are generally considered to be less than ideal for radiocarbon dating because they can ingest sediment while they graze, inadvertently consuming terrestrial carbon in the process. However, few studies of 14 C activity in herbivores or deposit-feeding gastropods have been conducted into this diverse ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 34 publications
0
37
0
Order By: Relevance
“…Hogg et al (1998) observed a similar pattern in 14 C variability in suspension-feeding and carnivorous shellfish and they attributed this to the complex of the intertidal region. Petchey et al (2012) analysed the 14 C marine reservoir variability in herbivores and deposit-feeding gastropods from archaeological context in Papua New Guinea and found that, although herbivorous shellfish are not considered ideal for radiocarbon dating, habitat preferences influence significantly their carbon content. Dating Thais sp.…”
Section: Brazilian Coastline and Previous Studiesmentioning
confidence: 99%
“…Hogg et al (1998) observed a similar pattern in 14 C variability in suspension-feeding and carnivorous shellfish and they attributed this to the complex of the intertidal region. Petchey et al (2012) analysed the 14 C marine reservoir variability in herbivores and deposit-feeding gastropods from archaeological context in Papua New Guinea and found that, although herbivorous shellfish are not considered ideal for radiocarbon dating, habitat preferences influence significantly their carbon content. Dating Thais sp.…”
Section: Brazilian Coastline and Previous Studiesmentioning
confidence: 99%
“…Site) and Type-3 (Fal-4) samples from the Falasarna region (Table 1) plot consistently with Type-1 beachrock from Falasarna (FAS) published by Pirazzoli et al (1996) and Shaw et al (2008). shells of marine organisms through ingestion of pre-existing carbon in their food source. In areas where carbonate bedrock is the dominant substrate, which is often the case in Crete, organisms that browse on encrusting algae, bedrock detritus, bore into the substrate or predate any of these organisms are capable of ingesting "old" carbon (Kidwell et al, 2005;Krause et al, 2010;Petchey et al, 2012). To reduce the potential impact of "old" carbon, where possible we have restricted radiocarbon samples to filter-feeding fauna or photosynthesising coralline algae.…”
Section: Dating Of Beachrockmentioning
confidence: 99%
“…The residence time of fossil shells prior to their cementation in beachrock has not been examined in detail here. Previous studies indicate that these residence times may be hundreds or even >1000 yr (e.g., Resig, 2004;Petchey et al, 2012) and depend mainly on the recurrence intervals of major storm events (e.g., Dezileau et al, 2011;Sabatier et al, 2012), the water temperature (e.g., shells within warm water environments, such as those recorded in the Mediterranean, have shorter residence times within a deposit; Petchey et al, 2012) and/or the nature of the environment (e.g., residence time in carbonate environments is shorter than in siliciclastic environments; Kidwell et al, 2005). Residence time may be partly reflected in the grain-size distribution of the beachrock, with comminution of original shells to sand-sized grains potentially requiring greater residence time than beachrock comprising mainly intact shells.…”
Section: Dating Of Beachrockmentioning
confidence: 99%
“…These are discussed in Ascough, Cook, and Dugmore (), who also address the use of tephra onshore/offshore isochrons for MRE determination and the suitability of marine and terrestrial material (see McFadgen, for a discussion on the old‐wood effect). Ascough, Cook, Dugmore, Scott, and Freeman () provide a discussion of possible confounding factors in shell radiocarbon measurement such as species‐dependent feeding habits and habitats (see, e.g., Dye, ; Forman & Polyak, ; Hogg et al, ; Petchey et al, ). Russell, Cook, Ascough, Barrett, and Dugmore () compare results obtained from a mollusk and a fish species.…”
Section: Methodological Approaches To Assessing the Mrementioning
confidence: 99%